Proteomics in cerebrospinal fluid and spinal cord suggests UCHL1, MAP2 and GPNMB as biomarkers and underpins importance of transcriptional pathways in amyotrophic lateral sclerosis - Oeckl, Patrick; Weydt, Patrick; Thal, Dietmar R.; Weishaupt, Jochen H.; Ludolph, Albert C.; Otto, Markus (Acta neuropathologica, 2020)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease and the proteins and pathways involved in the pathophysiology are not fully understood. Even less is known about the preclinical disease phase. To uncover new ALS-related proteins and pathways, we performed a comparative proteomic analysis in cerebrospinal fluid (CSF) of asymptomatic (n = 14) and symptomatic (n = 14) ALS mutation carriers and sporadic ALS patients (n = 12) as well as post-mortem human spinal cord tissue (controls: n = 7, ALS, n = 8). Using a CSF-optimized proteomic workflow, we identified novel (e.g., UCHL1, MAP2, CAPG, GPNMB, HIST1H4A, HIST1H2B) and well-described (e.g., NEFL, NEFH, NEFM, CHIT1, CHI3L1) protein level changes in CSF of sporadic and genetic ALS patients with enrichment of proteins related to transcription, cell cycle and lipoprotein remodeling (total protein IDs: 2303). No significant alteration was observed in asymptomatic ALS mutation carriers representing the prodromal disease phase. We confirmed UCHL1, MAP2, CAPG and GPNMB as novel biomarker candidates for ALS in an independent validation cohort of patients (n = 117) using multiple reaction monitoring. In spinal cord tissue, 292 out of 6810 identified proteins were significantly changed in ALS with enrichment of proteins involved in mRNA splicing and of the neurofilament compartment. In conclusion, our proteomic data in asymptomatic ALS mutation carriers support the hypothesis of a sudden disease onset instead of a long preclinical phase. Both CSF and tissue proteomic data indicate transcriptional pathways to be amongst the most affected. UCHL1, MAP2 and GPNMB are promising ALS biomarker candidates which might provide additional value to the established neurofilaments in patient follow-up and clinical trials.
Published: 07 November 2019
Gesehen am 16.06.2021